PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING BERBANTUAN MEDIA MANIPULATIF CUISENAIRE RODS UNTUK MENDUKUNG MINAT BELAJAR SISWA PADA MATERI BARISAN ARITMATIKA - Kumala, Rizka Dwi Kumala; Suesthi Rahayuningsih; Ulil Nurul Imanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe teacher activity, student activity, and students' learning interest in the implementation of the Creative Problem Solving learning model assisted by Cuisenaire Rods manipulative media on arithmetic sequence material. The study was motivated by the finding that mathematics learning at the junior high school level in Mojokerto still faced various challenges, including suboptimal learning outcomes and students' persistent errors in solving problems, indicating the need for a more active learning model supported by media that could help students understand concepts concretely. This research used a quantitative approach with a one-shot case study design, conducted at MTs Manba'ul Ulum with 20 students of class VII-A as research subjects. Data were collected through teacher activity observation sheets, student activity observation sheets, and a learning interest questionnaire, then analyzed descriptively and quantitatively. The results showed that teacher activity reached 89.29%, categorized as very good, student activity reached an average of 76.71%, categorized as good, while students' learning interest was dominated by the medium category with 8 students (40%). These findings indicated that the implementation of the CPS model assisted by manipulative media was carried out very well in terms of teacher activity and well in terms of student activity, although students' learning interest remained at the medium category because students were still adapting to the model and media used for the first time.